Shall we adopt the information about firms in facebook? - Loureiro, S.; Kaufmann, H. (12th International CIRCLE Conference for Consumer Behaviour and Retailing Research Book of Abstracts, 2015)
The adoption of information in Facebook is a subject of growing interest for both researchers and managers. Nevertheless, research in this area is still sparse and even core issues, such as the kinds of information available and how that information influence business relationships and partnerships, are not yet fully defined. Therefore, the purpose of this study is to analyse factors that lead consumers to adopt the information about products/brands. Findings show that timeliness, trustworthiness and importance of the SNS are the strongest drivers to information adoption.